Yellowmargined Leaf Beetle, Microtheca ochroloma Stål (Insecta: Coleoptera: Chrysomelidae) - Thomas R. Fasulo (EDIS)
The yellowmargined leaf beetle, Microtheca ochroloma Stål, is a pest of cruciferous crops and was first recorded in the United States from Mobile, Alabama, in March 1947, where it was found feeding on turnip, cabbage, collard, mustard, and radish (Chamberlin and Tippin 1949). It can devastate high value crops such as mizuna and mibuna (Japanese leafy vegetables), napa cabbage, turnip and watercress (Bowers 2003). This document is EENY-348, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 2005.